Determination of steroid hormones in human hair as a retrospective biomarker with HPLC-MS/MS - Wei Gao (European Journal of Psychotraumatology, 2012)
Statement of the problem : The analysis of steroid hormones in hair is increasingly used in psychoneuroendocrinological research as a valid and easily implementable method for the retrospective assessment of cumulative long-term hormone secretion. To determine steroid hormone concentrations in hair, most laboratories have so far relied on immunochemical assays which are fast and easy to perform, but have a reduced reliability and analytical specificity due to cross-reactivity with other substances. Furthermore, immunoassay can only measure a single steroid at one time. By contrast, liquid chromatography tandem mass spectrometry (LC-MS/MS) has better specificity, sensitivity and reproducibility, and can measure a wide spectrum of steroid hormones simultaneously. Here, we report data on the development of a new LC-MS/MS-based method for the identification of endogenous concentrations of seven steroid hormones (cortisol, cortisone, testosterone, progesterone, corticosterone, DHEA, androstendione) in human hair. Methods : Hair samples were first washed with isopropanol. Steroid hormones were extracted from 10 mg whole hair by 1.8 ml methanol incubation at room temperature. One milliliter methanol was transferred to a new tube and evaporated to dryness. Then the extraction was resuspended with 0.25 ml water, 0.20 ml of which was injected into the machine for analysis. Results : The limits of detection were 0.1 pg/mg (cortisol), 0.1 pg/mg (cortisone), 0.4 pg/mg (testosterone), 0.9 pg/mg (progesterone), 0.4 pg/mg (corticosterone), 9.0 pg/mg (DHEA), 0.1 pg/mg (androstendione). Linear ranges were 0.5–100 pg/mg (cortisol), 0.5–100 pg/mg (cortisone), 2–100 pg/mg (testosterone), 4–100 pg/mg (progesterone), 2–100 pg/mg (corticosterone), 40–1000 pg/mg (DHEA) and 0.5–100 pg/mg (androstendione). Conclusions : This LC-MS/MS method provides a highly specific analytical strategy for the detection of seven endogenous hormones in human hair and is thus likely to further enhance the accuracy of future research in this field.